Penerbitan SKPI sebagai Indikator Ekspor Hasil Tangkapan Madidihang di PPN Ambon - Ruslan H. S. Tawari; Stany R. Siahainenia; Jacobus B. Paillin; Jesica S. Sarimolle (Universitas Pattimura, 2023)
The Fish Landing Certificate (SKPI) is an indicator for small-scale fishermen in exporting their catch. In accordance with article 2 of Permen No.13/MEN/2012 SKPI is an instrument derived from SHTI which aims to facilitate trade activities to eradicate IUU Fishing and ensure traceability of fish catches and ensure the conservation of sustainable management of fisheries resources. This study aims to analyze the amount of yellowfin tuna production based on fishing time and fishing area (DPI), analyze trends and distribution patterns of yellowfin tuna exports based on SKPI data at the Ambon Archipelago Fishery Port. Methods Data collection was carried out through observation and interviews with quantitative descriptive analysis and trend analysis. The results showed that the highest amount of yellowfin tuna production based on DPI was in WPP 715 and the fishing area with the least production was in WPP 718. The percentage of development trends in production of yellowfin tuna catches based on SKPI data showed that the highest percentage of production was in August and the lowest percentage of production was in May. Furthermore, for the flow of distribution of tuna exports from small-scale fishermen, they usually take care of the SKPI directly at the Ambon PPN harbor. After the required documents have been validated for completeness, the harbormaster will immediately issue an SKPI. After requirements documents are validated furthermore used to be sent to America, Vietnam and Japan.